2020
DOI: 10.1515/opag-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Potato (Solanum tuberosum L.) Varieties for Yield and Some Agronomic Traits

Abstract: AbstractA field experiment was conducted in the central highlands of Ethiopia to evaluate the performance of potato varieties for tuber yield and to identify a superior variety in tuber yield and yield components. The experiment was laid out in a randomized complete block design with three replications at two locations in the central highlands of Ethiopia during the 2017 main cropping season. The results of analysis of variance (ANOVA) showed the presence of highly significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 14 publications
13
28
0
Order By: Relevance
“…The local variety with improved management practices gave 22.2ton ha -1 . This is in line with the study of (Tessema et al, 2020;Jafar et al, 2020;Alo and Geremew, 2021;Hailu et al, 2020;Kassaw et al, 2021;Alo and Geremew, 2021b;Befikadu et al, 2019) which reported Belete superiority over other varieties. The yield of Belete was 26% lower of its potential yield (figure 1).…”
Section: Yield Performance Of Demonstrated Potato Varietiessupporting
confidence: 86%
“…The local variety with improved management practices gave 22.2ton ha -1 . This is in line with the study of (Tessema et al, 2020;Jafar et al, 2020;Alo and Geremew, 2021;Hailu et al, 2020;Kassaw et al, 2021;Alo and Geremew, 2021b;Befikadu et al, 2019) which reported Belete superiority over other varieties. The yield of Belete was 26% lower of its potential yield (figure 1).…”
Section: Yield Performance Of Demonstrated Potato Varietiessupporting
confidence: 86%
“…Among the varieties grown in the districts, the improved varieties Gudane (24.1%) and Bubu (21.3%) as well as the farmers' (local) cultivar Jarso (17.6%) were the major ones (Figure 2). The Gudane variety and Jarso cultivar were early maturing compared with the Bubu variety [41]. The Bubu and Gudane varieties had comparable average tuber yields.…”
Section: Commonly Grown Potato Cultivarsmentioning
confidence: 93%
“…Potato yield is typically associated with seed quality as well as site-specific interactions between cultivars and environment conditions. The effects of soil type [16], nutrients [17,18], crop management practices [19,20], cultivar [21,22], seed quality [1,23], and weather conditions [24][25][26] on potato production have been explored extensively. Recent studies that incorporated multi-source data in yield prediction and nitrogen (N) recommendations have achieved better results than studies based on remote sensing data alone.…”
Section: Introductionmentioning
confidence: 99%